Developing a Concept Inventory for Computer Science 2: What should it focus on and what makes it challenging? - Huggard, Meriel (IEEE, 2020)
This Work-In-Progress Research Paper reports on an international study that is being undertaken in order to develop a validated concept inventory for the second introductory computer science course (CS2). A concept inventory is a research-based multiple-choice test that measures a student’s knowledge of a set of concepts while also capturing conceptions and misconceptions they may have about the topic under consideration. Development of a concept inventory for a course requires identifying course topics that are both difficult and important. This paper details how the Delphi method is being used to develop a concept inventory for CS2; in particular, it focuses on the initial process of identifying the set of topics that should be covered by a concept inventory for CS2.
IEEE Frontiers in Education
Keywords: Concept inventory; Delphi method; Computer Science 2 (CS2); Assessment